(untitled) (Journal of Asian Geography, 2022)
Malaysia, as any other country, is constantly evolving in all facets of life, including architecture, economy, and culture. Despite that, the Malay settlement on the river’s fringe remains an early settlement due to the Malays' strong connections to agriculture and socio-culture. It is in the tropical zone and high rainfall areas that are often hit by floods when the monsoon season is approaching. This hydro hazard has become one of the major concerns for the government and non-government sectors. High floods lead to financial damage, and it is related to human life. Kelantan is one of the challenging catchment areas that mostly experiences floods and heavy rains. Floods in the Kelantan water catchment area are associated with misfortune and loss of life. This study reviews the damage and nightmares of Kota Bharu residents. Some of their settlements located in the city were badly damaged. The research methodology employs previous researchers' exploratory techniques focusing on the effects of natural calamities, as well as socioeconomic data from 350 local respondents collected during the field survey in April 2019, and observation analysis information commonly used by architects to evaluate the context of the discussion. These include physical, social, cultural, and public amenities, and the data gathered then was amalgamated using IBM SPSS V26, supplemented by interview techniques and pictorial documentation. The study found that the infrastructure system in the Kota Bharu is in very poor condition. The floods that occur every year affect the quality of life of the Malay community in Kota Bharu. Until now, the Malay community is still traumatised by the disaster.